Abulfat, Karimov - (:unkn) unknown (My University, 2026)
Abulfat Isa Karimov graduated from the Azerbaijan Institute of National Economy named after D. Bunyadzade in 1975 with a degree in Political Economy and a qualification as a Teacher of Political Economy. In 1990, he was awarded the degree of Candidate of Economic Sciences (PhD in Economics) by the Academic Council of Belarusian State University. In 1999, he attained the academic title of Associate Professor in Marketing and Management. Since 1975, Dr. Karimov has been working at the Azerbaijan University of Architecture and Construction (formerly the Azerbaijan Civil Engineering Institute). He began his academic career at the Department of Political Economy and subsequently served as Head of the Department from 1992 to 1994. He currently works as an Associate Professor at the Department of Economic Theory and Marketing. Dr. Karimov is the author of 2 monographs, 3 textbooks, more than 100 scientific articles, and several educational curricula. His research has been published in Azerbaijan, Türkiye, and Kazakhstan.